Factors associated with perceived loss of libido in people who inject opioids: Results from a community-based survey in France. (1st September 2018) - Briand Madrid, Laélia; Morel, Stéphane; Ndiaye, Khadim; Mezaache, Salim; Rojas Castro, Daniela; Mora, Marion; Olivet, Fabrice; Laporte, Virginie; Protopopescu, Camelia; Carrieri, Patrizia; Roux, Perrine
Highlights: This study investigates the impact of the type of opioids injected on libido. Type of questioning (online or face-to-face) shows libido is still a taboo subject. The type of opioid used plays a significant role in how serious the libido loss is. Buprenorphine appears to be the opioid with the weakest effect. Abstract: Background: Regular consumption of opioids exposes individuals to several side effects. One of these is a loss of libido, which has a negative impact on quality of life. We used a cross-sectional community-based survey of people who inject opioids to study factors associated with loss of libido, and more particularly the impact of the type of opioid injected. Methods: This secondary study was conducted throughout France in 2015 and involved 514 people who inject opioids. Self-reported sociodemographic characteristics, drug consumption, injection-related data and loss of libido were collected using a brief questionnaire administered either through face-to-face interviews or online. Two different models were used to identify factors associated with loss of libido: simple logistic regression and a two-step Heckman model. Results: Forty-three percent of the participants reported a loss of libido. The first model showed that filling in the questionnaire online (OR[95%CI] = 2.55[1.64;3.96]; p < 0.001), reporting that morphine sulfate (OR[95%CI] = 2.67[1.56;4.58]; p < 0.001) or methadone (OR[95%CI] = 2.50[1.13;5.56]; p = 0.030) was the opioid they injected most (versus buprenorphine), and reporting benzodiazepine use (OR[95%CI] = 1.62[1.07;2.44]; p = 0.033) were factors strongly associated with loss of libido. In the two-step, Heckman model which corrected for selection bias, along with these factors, reporting heroin as the opioid injected most was also strongly associated. Conclusion: Our findings showed that full-opioid agonists could have a negative impact on libido when injected regularly. Libido can improve quality of life and should be routinely discussed through counseling in prevention services with people who inject drugs.